Parallel Mesh Adaptive Techniques Illustrated with Complex Compressible Flow Simulations - Pénélope Leyland; Angelo Casagrande; Yannick Savoy (Modelling and Simulation in Engineering)
The aim of this paper is to discuss efficient adaptive parallel solution techniques on unstructured 2D and 3D meshes. We concentrate on the aspect of parallel a posteriori mesh adaptation. One of the main advantages of unstructured grids is their capability to adapt dynamically by localised refinement and derefinement during the calculation to enhance the solution accuracy and to optimise the computational time. Grid adaption also involves optimisation of the grid quality, which will be described here for both structural and geometrical optimisation.